Glutathione and Glutaredoxin-Key Players in Cellular Redox Homeostasis and Signaling - Yuh-Cherng Chai; John J. Mieyal (MDPI AG, 2023)
This Special Issue of Antioxidants on Glutathione (GSH) and Glutaredoxin (Grx) was designed to collect review articles and original research studies focused on advancing the current understanding of the roles of the GSH/Grx system in cellular homeostasis and disease processes. The tripeptide glutathione (GSH) is the most abundant non-enzymatic antioxidant/nucleophilic molecule in cells. In addition to various metabolic reactions involving GSH and its oxidized counterpart GSSG, oxidative post-translational modification (PTM) of proteins has been a focal point of keen interest in the redox field over the last few decades. In particular, the S-glutathionylation of proteins (protein-SSG formation), i.e., mixed disulfides between GSH and protein thiols, has been studied extensively. This reversible PTM can act as a regulatory switch to interconvert inactive and active forms of proteins, thereby mediating cell signaling and redox homeostasis. The unique architecture of the GSH molecule enhances its relative abundance in cells and contributes to the glutathionyl specificity of the primary catalytic activity of the glutaredoxin enzymes, which play central roles in redox homeostasis and signaling, and in iron metabolism in eukaryotes and prokaryotes under physiological and pathophysiological conditions. The class-1 glutaredoxins are characterized as cytosolic GSH-dependent oxidoreductases that catalyze reversible protein S-glutathionylation specifically, thereby contributing to the regulation of redox signal transduction and/or the protection of protein thiols from irreversible oxidation. This Special Issue includes nine other articles: three original studies and six review papers. Together, these ten articles support the central theme that GSH/Grx is a unique system for regulating thiol-redox hemostasis and redox-signal transduction, and the dysregulation of the GSH/Grx system is implicated in the onset and progression of various diseases involving oxidative stress. Within this context, it is important to appreciate the complementary functions of the GSH/Grx and thioredoxin systems not only in thiol-disulfide regulation but also in reversible S-nitrosylation. Several potential clinical applications have emerged from a thorough understanding of the GSH/Grx redox regulatory system at the molecular level, and in various cell types in vitro and in vivo, including, among others, the concept that elevating Grx content/activity could serve as an anti-fibrotic intervention; and discovering small molecules that mimic the inhibitory effects of S-glutathionylation on dimer association could identify novel anti-viral agents that impact the key protease activities of the HIV and SARS-CoV-2 viruses. Thus, this Special Issue on Glutathione and Glutaredoxin has focused attention and advanced understanding of an important aspect of redox biology, as well as spawning questions worthy of future study.